KEDUDUKAN DAN KEKUATAN HUKUM WARISAN TUNGGU TUBANG MENURUT ADAT SEMENDE - Meita Djohan OE (Universitas Bandar Lampung (UBL), 2018)
Customary law as a regional culture is a nation's wealth that needs to be given special attention, especially when talking about preservation and introducing it to children. Introducing culture to young people, especially children, is done in various ways. The research issues to be discussed in this paper are Legal Status and Legal Strength of Wait Tubang According to Semende custom. The method of juridical normaatif and empirical research, using secondary and primary data, obtained from the study kepustakaaan and field studies, and data analysis with qualitative analysis. Based on the results of research and discussion it is known that Tunggu tubang is only valid in semende, until now the law of inherit waiting tubang still run according to custom semende, if power and position of law of customary inheritance of semende according to society semende or according to national inheritance law, recognized juridically in regulation Legislation in accordance with article 18B paragraph 2 (2) which reads: